A Teleradiology System for Early Ischemic and Hemorrhagic Stroke Evaluation and Management - Kalyanpur, Arjun; Mathur, Neetika (Journal of Clinical Interventional Radiology ISVIR, 2023)
Purpose Stroke is a cardinal cause of death and disability globally. It is an emergency condition where the rapidity of diagnosis is directly linked to the outcome. “Imaging is Brain” is, therefore, an important concept. The early diagnosis of stroke is crucial not only in guiding its effective treatment but also in estimating prognosis. This study aims to provide perspective on the implementation of international teleradiology in stroke evaluation, management, and care.Methods A dedicated international teleradiology stroke network has been evaluated in our study between March 2019 and July 2022 where the interpretation and analysis of the computed tomography (CT) scans of the patients from distant hospitals in United States were performed by teleradiologists via high-quality Digital Imaging and Communications in Medicine (DICOM)-image transfer through a cloud-based radiology information system/picture archival and communication system platform RADspa.Results Over a period of three and a half years, starting from March 2019, a total of 30,406 CT scans of 19,342 patients from 96 hospitals of 15 states in the United States were interpreted and reported by board-certified radiologists empaneled by Teleradiology Solutions. The mean report turnaround time for all noncontrast CT studies was 9.97 minutes at 95% confidence interval (CI: 9.89–10.05); for CT angiogram studies, it was 20.57 minutes 95% CI (20.38–20.77); and for CT perfusion studies, it was 13.72 minutes 95% CI (13.42–14.03).Conclusion A dedicated international teleradiology stroke network designed in our study allowed for transmission, prioritization, evaluation, and management of CT cases performed in the setting of acute stroke in the study population. The results of our investigation indicate that teleradiology provides an effective solution for early diagnosis/interpretation of CT examinations performed internationally in the setting of acute stroke. This may further be used as a model or template for the development of a nationwide stroke network within our own country.
Keywords: stroke; turnaround time; teleradiology